The eurozone crisis and its impact on Asia - Michael Blomenhofer (2014)
This paper uses root cause analysis to identify the root causes of the eurozone crisis and compares it with the causes of the Latin American, the Asian, and the sub-prime mortgage crisis in the US. Similarities and differences are identified. The paper argues that the root causes of the eurozone crisis were overleveraging, and the flaws in the design of the economic and monetary union. Although the crisis began over three years ago, it is only recently (July 2012) that actions have been initiated to fix the design flaws and deepen integration. Implementing these reforms will require strong political will on the part of member countries as they involve handing over authority to supranational institutions. Treaty changes may also be required. Progress is, therefore, expected to be slow. Whether these efforts to move from the economic and monetary union round one (EMU 1) to EMU 2, can save the euro is still an open question. The paper also examines the various channels through which the eurozone crisis has impacted Asia and concludes that the overall adverse impacts have been manageable so far, but cautions that it could be more serious in the future.